Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 1735 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Formicidae", "Geometry POLYGON((136.230468 38.822590,139.042968 44.087585,140.712890 45.828799,143.964843 45.274886,146.689453 44.024421,145.810546 40.713955,142.294921 34.089061,135.878906 31.503629,131.044921 29.916852,128.232421 29.458731,127.617187 32.324275,129.814453 34.741612,134.121093 37.649034,136.230468 38.822590))" ] } The dataset includes 1735 records from 13 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0008834-160623103540712/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences